PENGARUH KEBIJAKAN INVESTASI DAN SOLVABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Ummi Mahmuda; Meti Zuliyana (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
This research aims to find out the influence of investment habits and solvency on dividend policy on multi-industry manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. This type of research is quantitative research and the type of data used is secondary data obtained by researchers indirectly from the research object. The data collection method used is documentation. The bound variable used is the dividend policy, while the free variable used is the Investment and Solvency Policy. The study used multiple linear regression analysis because statistical analysis and regression models had been tested first in classical assumption tests. The results showed that simultaneously showed that the Investment and Solvency Policy had no significant effect on the Dividend Policy. The results of the study partially showed that the Investment Policy and solvency had no significant effect on dividend policy. Keywords: Investment Policy, Solvency, Dividend Policy